Near-island biological hotspots in barren ocean basins - Jamison M. Gove (Nature Portfolio, 2016)
The Island Mass Effect (IME), where island proximity enhances phytoplankton biomass, remains a poorly understood phenomenon. Here, the authors show the IME is a common feature among Pacific reefs, driving increased production that creates biological hotspots in otherwise barren ocean basins.